Early mortality, epidemiological and clinical factors in seriously ill patients treated in Intermediate Care Units - Osmani Pérez Ortiz; Angel Antonio Urbay Ruíz; Elaine Teresa Gutiérrez Pérez; Lis Marlyn Rodríguez García; Ivette Irene Molina Linares; Ernesto Conyedo Vergel (Acta Médica del Centro)
Introduction: the identification of epidemiological and clinical factors related to early mortality allows us to draw up strategies and perfect action protocols and quality of care in Intermediate Care Units. Objective: to identify the epidemiological and clinical factors related to early mortality in patients treated in the Intermediate Care Unit. Methods: an observational, analytical, cross-sectional study was carried out at the “Arnaldo Milián Castro” Hospital between October 2019 and October 2022. All deaths (348) in the Intermediate Care Unit in the analyzed period were studied. Documentary analysis of medical records and descriptive and inferential, bivariate and multivariate statistics were used. Results: older adult patients increased the possibility of dying early 1.5 times and those with white skin three times, the latter with an 80% occurrence in this study. Patients with septic shock were six times more likely to die, those diagnosed with out-of-hospital bronchopneumonia five times more likely, and those with ischemic stroke, exacerbated respiratory disease, or decompensated heart failure four times more likely, respectively. Conclusions: early mortality was more frequent in individuals with white skin and age over 60 years; the emerging Intensive Care Unit as the place of origin and the history of high blood pressure, upper digestive bleeding, ischemic heart disease and diabetes mellitus predominated. The diagnosis at admission of upper digestive bleeding and intraventricular hemorrhage was more closely related to early mortality, and septic shock and multiple organ dysfunction were determining complications as well.